BIOLOGICAL PROPERTIES OF SANDY DESERT SOILS AND WAYS TO IMPROVE THEM (Scientific journal of the Fergana State University, 2026)
Efficient use of sandy desert lands violation of their natural biodiversity, еar after еar decrease in precipitation and wastewater are among the main hazards, resulting in reduced efficiency of pasture use on sandy desert lands, which leads to a decrease in soil fertility. Combating desertification and improving the efficiency of work on the restoration of degraded lands is an important task. In this regard, the biological activity of sandy desert soils under pasture forage plants using bioorganic fertilizers and hydrogel was studied during the research. This article presents field experiments using agrobiotechnology with plants of isene (Kochia prostrata), teresken (Ceratoides ewersmanniana), chagon (Halothamnus subaphylla), keyreuk (Salsola orientalis). The enzymatic activity (catalase, urease and invertase) of soils and the number of microorganisms (ammonifiers, spore-forming, actinomycetes, and microscopic fungi) under different variants were studied. The results showed that the enzymatic and microbiological activity increased compared to the control variant, in which bioorganic fertilizers and hydrogel were used. The correlation between urease and ammonifiers, as well as spore-forming bacteria, is very high.